A134 A MULTI-CENTRE RANDOMIZED CONTROLLED TRIAL TO COMPARE TWO BOWEL CLEANSING REGIMENS AFTER A COLONOSCOPY WITH INADEQUATE BOWEL PREPARATION - Sey, M (J Can Assoc Gastroenterol, 2021)
AIMS: Failed bowel preparation is common during colonoscopy, yet the optimal purgative regimen to use for the next attempt is unknown. The objective of this study was to compare the efficacy, tolerability, and safety of two regimens at supratherapeutic doses for use after failed bowel preparation. METHODS: A multi-centre phase III endoscopist blinded randomized controlled trial (NCT02976805) was conducted in patients who failed bowel preparation, using the US Multi-Society Task Force (USMSTF) definition of inability to exclude polyps >5 mm in size and requiring a shortened interval to next colonoscopy. Regimen A consisted of 15 mg of bisacodyl and 2 + 2 L of split dose polyethylene glycol electrolyte solution (PEG) and Regimen B consisted of 15 mg of bisacodyl and 4 + 2 L of split dose PEG. The primary outcome was adequate bowel preparation, defined as a Boston Bowel Preparation Scale (BBPS) total score ≥ 6 with all segment scores ≥ 2. Secondary outcomes were adequate bowel preparation using the USMSTF definition, median BBPS, adenoma detection (ADR), advanced adenoma detection (aADR), sessile serrated polyp detection (SSPDR), and cecal intubation (CIR). Adverse events were assessed at the time of the colonoscopy and 14 days later. RESULTS: Between February 2017 and December 2019, 250 subjects were screened at four academic centres in Canada, of which 195 were randomized: 96 to Regimen A and 99 to Regimen B. The mean (SD) age was 60.6 (11.4) years, 87 (45.1%) were female, and the median (IQR) total BBPS score at previous failed colonoscopy was 3 (1,4). Regimen B was not superior to Regimen A in achieving adequate bowel preparation using the BBPS definition (87.6% vs. 91.1%, p=0.45) or the USMSTF definition (85.4% vs 91.1%, p=0.24), nor was it superior with respect to the median BBPS score (7 vs 7, p=0.50), mean ADR (31.5% vs 37.8%, p=0.37), aADR (11.2% vs 18.9%, p=0.15), SSPDR (5.6% vs 8.9%, p=0.40) or CIR (92.1% vs 96.7%, p=0.19). Regimen A had a higher adherence rate (88.2% vs. 74.7%, p=0.02) and greater willingness to undergo the bowel preparation again (91.2% vs. 66.2%, p<0.001). The only serious adverse event occurred in a patient randomized to Regimen B who was admitted to hospital for vomiting after colonoscopy. CONCLUSIONS: Split dose 4L PEG with 15mg of bisacodyl is highly efficacious, well tolerated, and can be used for patients who previously failed first line bowel preparations. The additional 2L of PEG in Regimen B did not improve bowel preparation and was not as well tolerated. FUNDING AGENCIES: AMOSO Opportunities Grant, Pharmascence Inc.